Interpreting access to the Dinaledi Subsystem by Homo naledi: redefining the “Chute” as a labyrinth - van Rooyen, Lambert; Berger, Lee; Hawks, John; Jinnah, Zubair (My University, 2025)
A large assemblage of fossils attributed to the hominin species Homo naledi was originally discovered in the remote and difficult-to-access Dinaledi Subsystem of the Rising Star cave system, South Africa. Entry into this section by scientists and explorers has always been through a narrow and complex fissure network that includes a substantial vertical descent. This area was named the “Chute” and was described and illustrated in simplified form as a ~12 m vertical passage that gives direct access from the entry point into the chamber itself. However, due to the very constrained nature of the fissure network, previous descriptions of this space have not been based on detailed survey. In this paper, we provide the first detailed survey data and accurate spatial descriptions of the area between the Dragon’s Back and the Dinaledi Subsystem, showing the full complexity of the horizontal and vertical fractures and fissures that comprise the network connecting these spaces. To reduce misconceptions, we have renamed this space the “Chute Labyrinth” to highlight its true form. While some changes have occurred in the last 335 ka, these did not change the access from the rest of the cave into the Dinaledi Subsystem. The new spatial data and re-description of the space contextualize how Homo naledi individuals physically entered the Dinaledi Chamber via the Chute Labyrinth into the chambers below to dispose of their dead.
The first detailed study and mapping of the access and egress routes into and out of the Dinaledi Chamber, Rising Star Cave, South Africa and its implications for understanding the use of the space by Homo naledi.
Keywords: Homo naledi; Rising Star Cave; Dinaledi Chamber; Dragons Back Chamber; Chute Labyrinth